ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS III SDN 4 WANAKERTA PADA MATERI PERKALIAN - Jenal Mutaqin, Ejen; Pebianti Sopiana, Anggia (Bale Aksara, 2021)
This study aims to determine the ability of grade III students in understanding mathematical concepts in the material of multiplication.. This can be seen more clearly in questions number 1, 2, 4, 6, 7 and 8. On the items number 1, 2 and 8 there are 4 students or 21.05% who can answer the questions correctly. In the items number 3 and 5 there are 7 students or 36.84.31% of students answered correctly. In items number 4 and 7, there are 5 students or 26.31% of students who answered the questions correctly. In point 6 there are 2 students or 10.52% of students who are able to answer the questions correctly. In item 9 there are 9 students or 47.37% of students who are able to answer the questions correctly. And in item 10 there are 13 students or 68.42% of students who answered correctly.